The Duties of the Sub-district Head Regarding the Guidance and Supervision of Village Government Administration in Cikeusik Sub-district, Pandeglang Regency - Ratu Milah Hamdalah; Rakhmat Bakhtiar; Sururi Faturohman (ijd-demos, 2025)
Government Regulation No. 43 of 2014 concerning the Implementing Regulations of Law No. 6 on Villages (Article 154) outlines the Camat (Sub-district Head)'s duty to provide guidance and supervision regarding the administration of village governance. To further reinforce this duty, Government Regulation No. 17 of 2018 concerning Sub-districts was issued; Article 10, letter (g), reiterates the camat's responsibility to guide and oversee village governance administration. Issues have arisen in Cikeusik Sub-district where many villages lack the capacity to effectively administer village governance, resulting in delays to the evaluations conducted by the local government. This is significant because reports on village governance administration must include details on the previous year's operations, plans for the remaining five-month term, achievements, and areas requiring improvement. This study employs a qualitative research method. The findings indicate that while the Cikeusik Camat has carried out their duties, the performance has not been optimal. This is due to an excessive workload, making it difficult for the Camat to provide adequate guidance and supervision for village governance in the area. The situation is exacerbated by the large number of villages (fourteen) and challenging geographical conditions—including distance—which hinder the Camat's ability to conduct guidance and supervision. Additional obstacles include many village heads disregarding the Camat's directives and a lack of competence among village officials, which slows down the comprehension of guidance provided by the Camat or relevant agencies. Keywords: Duties, Sub-district Head (Camat), Guidance, Supervision, Governance, Village